Control de Sitophilus zeamais con polvos vegetales de tres especies del género Chenopodium - Silva-Aguayo, Gonzalo Ivan; Kiger-Melivilu, Rodrigo; Hepp-Gallo, Ruperto; Tapia-Vargas, Maritza (Pesquisa Agropecuaria Brasileira, 2005)
Powders of Chenopodium ambrosioides L., Chenopodium album L. and Chenopodium quinoa Willd. were evaluated under laboratory conditions for Sitophilus zeamais Motschulsky control. Evaluated parameters were insect mortality and adult emergence, grain weight loss, grain germination and the following effects of powders: ovicide and larvicide, fumigant, repellent and residual. A completely randomized experimental design with factorial arrangement and three replicates was used. The highest levels of insect mortality were obtained with the powders of Chenopodium ambrosioides L. inflorescence and the mixture of leaves and stems at 2% (w/w), with values of 69.4% and 67.9% respectively. Best emergence reductions were obtained with the same treatments. In all treatments with powders of C. ambrosioides seeds weight were reduced in less than 3%. The residual effect lasted for 15 days, obtaining a mortality of 98.3% of adult insects, when powders of C. ambrosioides inflorescence were used at 2% (w/w) concentration. Powders of C. ambrosioides showed a mortality of 100% of eggs and larvae, and a fumigation effect against adult insects with a mortality of 100% in all treatments was evaluated. Powders of C. ambrosioides have a repellent effect for S. zeamais.